Replication of the "Social Rituals and Mental Health: A Novel Approach to Early Intervention in Mental Illness" Project in an Iranian Setting - Azadeh Malekian; Gholamhosein Ahmadzadeh; Mohsen Maroufi; Abbas Attari; Amitice Bahramian; Aleksandar Janca (International Journal of Body, Mind and Culture, 2014)
Background: The present study is a replication of a study designed by the University of Western Australia (UWA). The hypothesis examined is that the deteriorating mental functioning which occurs during early stages of mental illness are recognizable in the form of altered sensitivity to expected rituals and an altered ability to perform the rituals appropriately. The present study aimed to evaluate the cultural applicability and feasibility of the Social Rituals Interview Schedule (SRIS) within the Iranian culture, and to assemble a culture-specific repertoire of social rituals in Iran. In addition, it aimed to examine the extent to which disturbances in everyday expected social rituals can be used for the early identification of individuals, families, and communities who have, or are at risk of soon developing, poor mental health. Methods: The SRIS domains of social rituals were discussed in an expert focus group discussion and during key informant interviews with mental health patients and their care-givers. Results: The concept of social rituals was acknowledged as being applicable and relevant in detecting early alterations in one's mental health condition. All domains of the SRIS were also confirmed as culturally applicable in the Iranian setting. A new domain named “Religious Rituals" was added to the domains already identified by UWA researchers as a significant and culturally sensitive domain of the social rituals in Iran. A culturally modified Farsi version of the SRIS -applicable and valid for use within the Iranian culture- was produced. Conclusion: Both the social rituals concept and the produced Farsi version of its Interview schedule were regarded as culturally applicable to provide a foundation for planning prospective tools for early recognition of mental health deterioration in Iranian settings.